INFORMATION COMMUNICATION TECHNOLOGY (ICT) BASED SCIENCE LEARNING TO INCREASE STUDENT CREATIVITY - Ikhsan, Muhammad; Jumadi, Jumadi; Pamungkas, Oky; Kurniawan, Lilik (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
This research aims to explore the use of Information and Communication Technology (ICT) in science learning to enhance student creativity, focusing on analyzing electronic teaching materials used at the secondary education level. Through a Systematic Literature Review (SLR) approach following PRISMA guidelines, this study identified and analyzed 32 scientific articles from Sinta, Scopus, and ScienceDirect databases relevant to the topic. The analysis showed that e-modules were the most widely used electronic teaching materials, with significant contributions to the improvement of 21st century skills, including creativity, critical thinking, and collaboration. This research also highlights the effectiveness of the project-based learning model in supporting students' creative skills development. By providing deep insight into the mechanisms of enhancing creativity through ICT integration in science learning, this study contributes to a better understanding of the role of technology in education and offers recommendations for more innovative teaching practices in the future.